2019
DOI: 10.1111/ahe.12427
|View full text |Cite
|
Sign up to set email alerts
|

Histological and anatomical variations of septomarginal trabecula in bovine hearts

Abstract: The use of hearts from different animals as models in the experimental pharmacology and surgical clinic has led, in recent years, to an increase on interest of research with this organ. The heart’s conducting system, from the septomarginal trabecula, presents several variations, which generates numerous controversies in the literature. So, the objective of the present study is to analyse the morphology of the septomarginal trabecula of bovine hearts, identifying possible macro‐ and microscopic variations. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In the literature, it has been reported that the right septomarginal trabecula extends between the septum—outer wall (Evans & De Lahunta, 2013; Nascimento et al, 2019; Ravindran & Victor, 1982) septum—anterior papillary muscle (Ghonimi et al, 2015; Kosinski et al, 2010; Leao et al, 2010; Nascimento et al, 2019; Raghavendra et al, 2013), anterior papillary muscle—outer wall (Arıncı & Elhan, 2014; Ateş & Çakır, 2010; Cope, 2016b; Evans & De Lahunta, 2013), and septal papillary muscle—anterior papillary muscle (Ates et al, 2017; Gulyaeva & Roshchevskaya, 2012; Perez et al, 2018). In our study, it was determined that the right septomarginal trabecula extended between the septal papillary muscle and the anterior papillary muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, it has been reported that the right septomarginal trabecula extends between the septum—outer wall (Evans & De Lahunta, 2013; Nascimento et al, 2019; Ravindran & Victor, 1982) septum—anterior papillary muscle (Ghonimi et al, 2015; Kosinski et al, 2010; Leao et al, 2010; Nascimento et al, 2019; Raghavendra et al, 2013), anterior papillary muscle—outer wall (Arıncı & Elhan, 2014; Ateş & Çakır, 2010; Cope, 2016b; Evans & De Lahunta, 2013), and septal papillary muscle—anterior papillary muscle (Ates et al, 2017; Gulyaeva & Roshchevskaya, 2012; Perez et al, 2018). In our study, it was determined that the right septomarginal trabecula extended between the septal papillary muscle and the anterior papillary muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In another study (Lee & Hur, 2019), right septomarginal trabeculae were classified ‘cylindrical’ in seven, ‘long and thin’ in 15, ‘wide and flat’ in 14 hearts, and it was reported that they did not find this band in two hearts. It was stated that the right septomarginal trabeculae in bovine (Nascimento et al, 2019) were tubular fibromuscular structure. It was determined that septomarginal trabeculae were fleshy in camel (Ghonimi et al, 2014), in buffalo (Ghonimi et al, 2015), and goats (Leao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, trabecula septomarginalis also has a role in preventing excessive ventricular expansion during the systole stage. C. titthaecheilus has a branched type of trabecula septomarginalis, which connects the septum interventricularis and right ventricle that differs from that found in other animals such as cattle (Nascimento 2019), pigs (Ates et al 2017;Gulyaeva 2012), dogs (Bombonato 2012;Cope 2015 ), camels (Ghonimi 2014) and buffalo (Ghonimi 2015); most of them have a single trabecula septomarginalis, but ostrich has variation number trabecula septomarginalis (Tadjalli et al 2009). According to its role in transmitting electrical impulses and preventing excessive expansion of the ventricular wall, the branches trabecula septomarginalis owned by bats, are assumed as an effort to adapt the bat's heart to be able to work harder in meeting the needs of blood flow when flying.…”
Section: Discussionmentioning
confidence: 99%
“…Its function is to prevent distension of the right ventricle and to transmit the right branch of the atrioventricular bundle to the right ventricle. Furthermore, the ST has an important role in the contraction and relaxation of the ventricles [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%